2007
DOI: 10.1016/j.yexcr.2007.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TGF-β1/MAPK-mediated PAI-1 gene expression by the actin cytoskeleton in human mesangial cells

Abstract: The importance of transforming growth factor-beta1 (TGF-beta1) in plasminogen activator inhibitor-1 (PAI-1) gene expression has been established, but the precise intracellular mechanisms are not fully understood. Our hypothesis is that the actin cytoskeleton is involved in TGF-beta1/MAPK-mediated PAI-1 expression in human mesangial cells. Examination of the distributions of actin filaments (F-actin), alpha-actinin, extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) by immunofluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…These results, for the first time, confirmed that the activation of the JNK pathway by hydrostatic pressure may be negatively regulated by RhoA and Rac1. Previous studies have shown that there were associations between active phosphorylated JNK and stress fibers in cells (Hamel et al, 2006;Yang et al, 2007). Furthermore, a proximity ligation assay demonstrated the co-localization of phospho-JNK and F-actin under mechanical stimulation (Mengistu et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…These results, for the first time, confirmed that the activation of the JNK pathway by hydrostatic pressure may be negatively regulated by RhoA and Rac1. Previous studies have shown that there were associations between active phosphorylated JNK and stress fibers in cells (Hamel et al, 2006;Yang et al, 2007). Furthermore, a proximity ligation assay demonstrated the co-localization of phospho-JNK and F-actin under mechanical stimulation (Mengistu et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…S6B). Because there are several crosstalks between Smad pathways and MAPK pathways including JNK (37,38), JNK might also be positively involved in the induction of autophagy genes in addition to the Smad pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The data can be interpreted as indicating that preconditioning with rHMGN2 inhibits cofilin phosphorylation, and then induces actin disruption which may block ERK phosphorylation. [38][39][40] Recent studies have shown that actin stress fiber formation was increased by inhibiting ERK phosphorylation, 41) and ERK dephosphorylation can result from inhibition of the cofilin kinase(s), which in turn induces actin depolymerization. In our experimental system, HMGN2 can not completely inhibit actin polymerization.…”
Section: Discussionmentioning
confidence: 99%